The use of communication platforms and cognitive heuristics in political decision making of Thailand novice voters - Khunsiri, Wisut; Pattanachatchai, Napapan; Nanthawatsiri, Pastkorn; Thiamsakul, Sumathee; Intaratat, Dungkamol (Edelweiss Applied Science and Technology, 2025)
This study investigates the role of online media in shaping the political decision-making process among novice voters in Thailand, particularly Generation Z. Given the increasing reliance on digital platforms, understanding the factors influencing their political perceptions and party loyalty is crucial. The study aims to (1) examine the most influential political communication platforms among eligible voters, (2) identify key political information that voters retain, (3) analyze decision-making processes in selecting political representatives, and (4) explore factors contributing to novice voter loyalty. Employing a mixed-methods approach, data were collected from Generation Z university students across Thailand (excluding the southern region) through online questionnaires. Findings indicate that social media platforms, particularly Facebook, TikTok, X, and YouTube, play a dominant role in political information dissemination. Novice voters exhibit limited political knowledge but rely on cognitive heuristics, such as party imagery, influencer endorsements, and polling trends, to form opinions. Moreover, emotional attachment significantly outweighs rational analysis in their decision-making, leading to sustained party loyalty even in the face of ethical or legal controversies. The study underscores the need for enhanced media literacy education to equip young voters with critical thinking skills for political information assessment. Parents and educators should promote digital literacy, fact-checking, and rational decision-making to counter misinformation. These findings contribute to a deeper understanding of youth political engagement and offer insights for policymakers in refining communication strategies in the digital era.